Unity Artificial Intelligence Programming: Add powerful, believable, and fun AI entities in your game with the power of Unity - Aversa, Davide (Packt Publishing, 2022)
Learn and implement game AI in Unity to build smart environments and enemies with A* pathfinding, finite state machines, behavior trees, and the NavMesh Key Features Explore the latest Unity features to make AI implementation in your game easierBuild richer and more dynamic games using AI concepts such as behavior trees and navigation meshesImplement character behaviors and simulations using the Unity Machine Learning toolkit Book Description Developing artificial intelligence (AI) for game characters in Unity has never been easier. Unity provides game and app developers with a variety of tools to implement AI, from basic techniques to cutting-edge machine learning-powered agents. Leveraging these tools via Unity's API or built-in features allows limitless possibilities when it comes to creating game worlds and characters. The updated fifth edition of Unity Artificial Intelligence Programming starts by breaking down AI into simple concepts. Using a variety of examples, the book then takes those concepts and walks you through actual implementations designed to highlight key concepts and features related to game AI in Unity. As you progress, you’ll learn how to implement a finite state machine (FSM) to determine how your AI behaves, apply probability and randomness to make games less predictable, and implement a basic sensory system. Later, you’ll understand how to set up a game map with a navigation mesh, incorporate movement through techniques such as A* pathfinding, and provide characters with decision-making abilities using behavior trees. By the end of this Unity book, you’ll have the skills you need to bring together all the concepts and practical lessons you’ve learned to build an impressive vehicle battle game. What you will learn Understand the basics of AI in game designCreate smarter game worlds and characters with C# programmingApply automated character movement using pathfinding algorithm behaviorsImplement character decision-making algorithms using behavior treesBuild believable and highly efficient artificial flocks and crowdsCreate sensory systems for your AI worldBecome well-versed with the basics of procedural content generationExplore the application of machine learning in Unity Who this book is for This Unity artificial intelligence book is for Unity developers with a basic understanding of C# and the Unity Editor who want to expand their knowledge of AI Unity game development.